2017
DOI: 10.12659/msm.903500
|View full text |Cite
|
Sign up to set email alerts
|

TRAF2 is a Valuable Prognostic Biomarker in Patients with Prostate Cancer

Abstract: BackgroundTRAF2 exerts important functions in regulating the development and progression of cancer. The aim of this study is to investigate whether TRAF2 is a valuable prognostic biomarker and to determine if it regulates TRAIL-induced apoptosis in prostate cancer.Material/MethodsMicroarray gene expression data from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases were used to determine TRAF2 expression in prostate cancer. TRAF2 expression in prostate cancer was further investigated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…In recent years, many investigations concentrated on finding variant biomarkers in the prostate carcinogenesis progression. For example, matrix metalloproteinase‐26 and tumour necrosis factor receptor‐associated factor 2 have been identified (Cheng et al, ; Wei et al, ). Despite great progress has been made, the molecular mechanism of prostate cancer is far from being completely explained.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many investigations concentrated on finding variant biomarkers in the prostate carcinogenesis progression. For example, matrix metalloproteinase‐26 and tumour necrosis factor receptor‐associated factor 2 have been identified (Cheng et al, ; Wei et al, ). Despite great progress has been made, the molecular mechanism of prostate cancer is far from being completely explained.…”
Section: Introductionmentioning
confidence: 99%
“…A prostate cancer study showed that up regulation of TRAF2 associated with poor recurrence of metastatic cancer. (16) TNF-α which contained in CM could induce NF-κB through canonical pathway. Lately, breast cancer study proved that higher NF-κB expression lead to proliferation of MDA-MB-468.…”
Section: Discussionmentioning
confidence: 98%
“…This shows that there is a strong correlation between TRAF2 and TRAF6 and immune infiltration. In addition, TRAF2 is upregulated in breast cancer, pancreatic cancer, and other malignant tumors [ 41 , 42 ] and is significantly related to the prognosis of patients with prostate cancer [ 43 ]. Zhang et al found that IL12A showed significantly high expression in differentiated thyroid cancer, was associated with disease invasiveness, and was an independent predictor of the prognosis of differentiated thyroid cancer [ 44 ].…”
Section: Discussionmentioning
confidence: 99%